2007
DOI: 10.1111/j.1445-2197.2006.03979.x
|View full text |Cite
|
Sign up to set email alerts
|

NATIONAL BREAST CANCER AUDIT: DUCTAL CARCINOMA IN SITU MANAGEMENT IN AUSTRALIA AND NEW ZEALAND

Abstract: There was predominantly close adherence to recommendations with three possible areas of improvement: fewer axillary procedures, an appraisal of radiotherapy practice following BCS and more investigation into tamoxifen prescription practices for DCIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
3
14
2
Order By: Relevance
“…These data support clinical audit by surgeons of their practices and are used for research into breast cancer and its management. [1][2][3][4][5] It is evident that the value of the NBCA database would be enhanced if data on survival outcomes could be included. This would allow comparisons of outcomes by cancer characteristic, treatment practice and potentially by case load and other provider characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These data support clinical audit by surgeons of their practices and are used for research into breast cancer and its management. [1][2][3][4][5] It is evident that the value of the NBCA database would be enhanced if data on survival outcomes could be included. This would allow comparisons of outcomes by cancer characteristic, treatment practice and potentially by case load and other provider characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The data support clinical audit by surgeons of their practices and are used for research into breast cancer and its management. [1][2][3][4][5] The Audit's main purpose is to strengthen quality improvement through the promotion of high clinical standards, but it is recognised that cancer outcomes would also be affected by structural features of the health system, potentially including governance structures, resource allocation, service coordination, workforce availability, and access and appropriateness of care. [6][7][8] For example, poor survival from cancer among Aboriginal and Torres Strait Islander patients has been associated with geographic remoteness, cultural differences, socioeconomic and other social factors not adequately accommodated by the health system, rather than technical standards of care delivered.…”
Section: Introductionmentioning
confidence: 99%
“…The 2007 UK/New Zealand trial evaluating the use of tamoxifen in DCIS was the first to demonstrate a reduction in CBC with tamoxifen. 9 After publication of this study, recommendations for consideration of the use of anti-e were extended to patients undergoing mastectomy to reduce the risk of CBC. 22 We have shown that most patients (76%) undergo lumpectomy for ER+ DCIS.…”
Section: Discussionmentioning
confidence: 99%